Um algoritmo de decisão de Handover baseado em QoS e autonomia energética - Silva, Sávio Roberto Amorim Aragão (2015)
A key step in the handover process corresponds to the decision phase in which the mobile device selects the candidate network that it will be attached to. The criterion generally used in the decision step is the signal strength of the available network. In addition to the signal power, other criteria also need to be explored in heterogeneous environments for taking handover decision, since the network technologies differ in the types of services, protocols, quality standards, frequency bands and monetary costs. This paper proposes a handover decision algorithm based on cost function that takes into account both the received signal power, some quality of service criteria such as packet loss rate, delay and jitter, as well as the energy consumption of network interface of the mobile station. In order to evaluate the performance of the algorithm were considered two scenarios, one in which the battery of device mobile is sufficiently charged and another where it meets the low load. Simulations in NS-2 were performed in an environment compound by the Wi-Fi and WiMAX networks. The results showed that the proposed algorithm helped to reduce the number of wrong handovers decisions, so that there was no deterioration in the quality of service that would affect the performance of the network in which the mobile device is currently connected.